Integrated Wastewater Processing using Electrogoagulation Method into Oxyhydrogen (HHO) for Renewable Energy - Rusdianasari Rusdianasari; Ahmad Taqwa; Aida Syarif; Yohandi Bow (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Integrated wastewater is one of the contributors to wastewater that can harm the environment, thus fast industrial expansion must be followed by advancements in wastewater processing systems. Because the presence of contaminants in integrated wastewater can cause several issues for persons and the environment, integrated wastewater processing is required. One type of integrated wastewater processing is the production of hydrogen gas as a new and sustainable energy source. The electrocoagulation process may be used to convert integrated wastewater into hydrogen gas. One type of integrated wastewater processing is the production of hydrogen gas as a new and sustainable energy source. The electrocoagulation process may be used to convert integrated wastewater into hydrogen gas. In this study, oxyhydrogen (HHO) was produced from integrated wastewater utilizing two process stages: integrated wastewater processing with an electrocoagulator, followed by the process of getting HHO using an oxyhydrogen reactor. A NaOH catalyst was applied at different concentrations of 0.1 M, 0.2 M, 0.3 M, 0.4 M, and 0.5 M with an electrolysis period of 5 minutes to produce hydrogen gas. The addition of the NaOH catalyst is intended to find the optimal concentration for the production of hydrogen gas. According to the findings of the study and analysis, the optimal NaOH catalyst concentration for producing hydrogen gas is 0.5 M with hydrogen content of 346 mg/m3.Keywords: electrocoagulation, oxyhydrogen, integrated wastewater, renewable energy